Meningkatkan Ketahanan Duduk Saat Proses Pembelajaran melalui Pemberian Reward kepada Siswa Autisme - Yolanda Ismudar; Damri Damri (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2021)
This study discusses the analysis of rewording in the form of stickers with star images, in increasing the duration of sitting endurance for autistic students during the learning process. This study used an experimental method with a single subject research approach. The subject of this study was a class VI autistic student who had a low duration of sitting resistance during the learning process in the classroom. Researchers made observations during seventeen meetings, all data were obtained through observation, interviews and action tests which were presented in graphic form. To measure the duration of sitting endurance, the researcher used a stopwarch analysis tool. Overall the results of the research on the initial conditions for five meetings were 2 minutes, 2 minutes, 4 minutes, 3 minutes 3 minutes. Furthermore, in the intervention condition during the seven meetings the researcher gave reword in the form of a star sticker image, the results were 4 minutes, 3 minutes, 4 minutes, 6 minutes, 5 minutes, 7 minutes, 8 minutes. At baseline A2 conditions obtained dudu resistance results After being given the treatment, namely 5 minutes, 5 minutes, 6 minutes, 7 minutes, 9 minutes. The results of this study prove that giving rewords in the form of star stickers in the learning process can increase the duration of sitting endurance for autistic students, but it is necessary to develop further research in this problem in different contexts and issues.